Farmer-led adaptation innovations are at the heart of CGIAR’s Livestock and Climate adaptation work - Ferrari, Mireille; Habermann, Birgit (CGIAR System Organization, 2022)
In the second half of 2022, researchers from the initiative organized workshops in Kenya (in Nandi county) and Ethiopia (in North Shew Zone in Amhara) to ensure that key stakeholders were on board with the priorities and planned activities that were shaped by previous consultations with them. The groups consisted of government officials, national research partners, farmer cooperatives (especially ones that included women and youth) and private sector organisations. The consultations were led by researchers from the International Livestock Research Institute (ILRI), the Alliance of Bioversity International and CIAT and ICARDA in sites that overlapped with other CGIAR initiatives such as Low-Emission Food Systems, Mixed Farming Systems and Sustainable Animal Productivity.